Are Normal Narcissists Psychologically Healthy? Self-Esteem Matters.[article]. - Sedikides, Constantine
Five studies established that normal narcissism is correlated with good psychological health. Specifically, narcissism is (a) inversely related to daily sadness and dispositional depression (b) inversely related to daily and dispositional loneliness, (c) positively related to daily and dispositional subjective well-being as well as couple well-being, (d) inversely related to daily anxiety, and (e) inversely related to dispositional neuroticism . More important, self-esteem fully accounted for the relation between narcisism and psychological health. Thus, narcissism is beneficial for psychological health only insofar as it is associated with high self-esteem. Explanations of the mainand mediational findings in terms of response or social desirability biasis (e. g., defensiveness, repression, impression management) were ruled out. Supplementary analysis showed that the links among narcissism, self-esteem and psychological health were preponderantly linear. -- (from the author)